Rancang Bangun Mesin Pengupas Buah Pohon Aren (Kolang-Kaling) - Rizki Ramdani; Agus Saleh; Yoddy Agung Nuhgraha; Muhammad Abdul Rofik (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is entitled "Design of the Peeler Palm Fruit on The Machine Making Sugar Palm Fruit ". Young palm fruit that is used as an ingredient to produce palm fruit has a hard skin and seeds that are very tightly attached to the fruit strands, so it takes several processes and a long time to process palm fruit into fruit palm fruit. The production of kolang-kaling is very low due to the application of post-harvest technology for palm fruit that is not optimal, therefore the technology for breaking palm fruit is applied in a way that is easy and safe to use. The design of the peeler on the sugar palm fruit making machine aims to help the community of kolang-kaling entrepreneurs in the process of processing sugar palm fruit which is still simple and takes a long time. The method used in this study uses an experimental method with a combination of qualitative and quantitative approaches while the data analysis technique used uses quantitative techniques. The design of the peeler on this sugar palm fruit machine uses the methods of analysis, design, assembly, and testing of the peeler. This research was conducted from November 2020 to June 2021 in Pasir Munjul Village, Sukatani District, Purwakarta Regency and in the Mechanical Engineering Practice Room TEDC Polytechnic Bandung. The parameters observed were the effective capacity of the tool (kg/hour). The results of the design obtained are a palm fruit crusher with dimensions of 600 mm x 1200 mm x 1000 mm which is integrated with the flattening tool and uses a 3600 rpm combustion motor power with a power of 5.5 HP with the principle of stripping using seven blades that rotate on its axis and the palm fruit rests on the runway gap. The results showed that the effective capacity of the tool was 918 kg/hour with stripping results of 139.5 kg/hour.